Digital Solutions and Machine Learning Can Improve Niche Market Reach - Somosi, Zoltán; Hajdú, Noémi (Theory, Methodology, Practice – Review of Business and Management, 2023)
Digital solutions in marketing can help reach niche markets. Marketers have the greatest opportunity ever to address segments whose needs have not yet been met. Online segmentation techniques allow to better know their characteristics. The aim of this article is to investigate the segmentation and targeting possibilities of the Google Ads system, which helps to explore consumer patterns more deeply. Digital marketing solutions help marketers reach niche markets to maximise the effectiveness of their activities. The goal of this social constructivist research was to find an answer to the question of whether the segmentation and targeting options of the Google Ads advertising system can sufficiently ensure this. To this end, we examined the presence of the “target market category” label in 37 individuals using a face-to-face survey method. The occurrence of the labels and the actual interests often overlapped.